PENGENDALIAN SOSIAL ORANG TUA PADA ANAK DALAM MENGGUNAKAN SMARTPHONE DI DUSUN SADONG KECAMATAN SUNGAI AMBAWANG - Sihombing, Teti Riyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis thesis is titled ?Parents Social Control on Children in Using Smartphones (The Study in Dusun Sadong, Sungai Ambawang District. A common problem of this research ishow the Parents Social Control on Children in Using Smartphones (The Study in Dusun Sadong, Sungai Ambawang District? As for the sub-issues: 1)how the parents repressive social control on children in using smartphones? And 2) how the parents persuasive social control on children in using smartphones?This research uses qualitative approach with descriptive method. Data collection techniques of observation, interview and documentation study with data collection tool of observation guide, interview guide, note book and archives. Informants in this research were parents and children. Positive impact for children using smartphones such as to facilitate children looking for tasks from school, entertainment, and introduce children to interact socially with peers through technology. However, the perceived impact is generally more negative impacts such as children less concentrated learning, lazy learning, declining learning outcomes, forgetful time, and others. The results of this research indicate that parents have done social control in children that are repressive and persuasive. Repressive social controls by parents on children in using smartphones through reprimands and punishment. Persuasive social controls by parents through invitations, appeals, directions, and guidance.  Keyword: Social Control, Repressive, Persuasive, Smartphones